STRATEGI PEMASARAN HOTEL DALAM MENGOPTIMALKAN POTENSI SLEEP TOURISM SEBAGAI DAYA TARIK WISATA BARU - Yuke Hernawati; Abdul Khalim (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
The growth of wellness tourism has contributed to the emergence of sleep tourism as a new trend within the tourism and hospitality industry. This phenomenon has developed alongside increasing public awareness of the importance of sleep quality as a fundamental component of health and well-being. Despite its growing popularity, studies examining hotel marketing strategies for developing sleep tourism remain limited, particularly in the Indonesian context. This study aims to analyze hotel marketing strategies in optimizing the potential of sleep tourism as a new tourism attraction. This research employed an exploratory qualitative approach using Thematic Analysis. Data were collected through semi-structured interviews, observations, documentation, and literature review involving two star-rated hotels in Cirebon, Indonesia, selected through purposive sampling. The findings revealed four major themes: (1) the potential of sleep tourism as a hotel product, (2) sleep tourism marketing strategies, (3) challenges in implementing sleep tourism, and (4) prospects and development opportunities. The results indicate that sleep quality can be transformed into a valuable tourism experience by providing supportive facilities, relaxing environments, and guest-oriented services. Furthermore, the development of sleep tourism requires integrating experience marketing, digital marketing, and wellness tourism principles to create product differentiation and sustainable competitive advantages for hotels. This study contributes to the growing body of literature on sleep tourism by proposing a conceptual framework for hotel marketing strategies that integrates perspectives from wellness tourism, experience marketing, and hospitality marketing in the Indonesian hospitality industry.